Performance Testing of Breakdown High Voltage Contactor - Hamdan, Muhammad Akram; Othman, Nordiana Azlin (Evolution in Electrical and Electronic Engineering, 2025)
The aim of this paper is to study the behaviour of a breakdown high voltage (HV) contactor with different insulating materials. The analysis of breakdown voltage and electric field distribution by means of experimental testing and numerical simulation is considered in the study. The purpose is to test the dielectric strength of various insulating materials that is to say acrylic heat shrink rods (Polyolefin), Teflon and uninsulated rods under high voltage stress. The experimental analysis was in a high-voltage laboratory and simulation analysis by using Comsol Multiphysics software. Based on the results, it was found out that the value of the dielectric strength went up sharply with the use of insulation. Precisely, there were low breakdown voltages by bare rods of 23 kV (at 12 mm gap) and 32 kV (at 16 mm gap) whereas the acrylic and Polyolefin insulators had more than 50 kV to break. The same respective distances after being tested, showed a breakdown voltage of 47kV and 49kV with teflon. The simulation results further justified that when you increase the electrode gap it decreases the strength of the electric field, and also full insulation coverage results in widespread field distribution in comparison to partial insulation. This highlights the devastating effect of the insulation material used, how well one insulates, and the spacing between the electrodes of the dielectric behavior. In summary, the reliability and safety of high-voltage contactor systems could be increased greatly by insulating using suitable materials and arrangements.